2022
DOI: 10.3390/nu14214522
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality among Students Attending an Australian University Is Compromised by Food Insecurity and Less Frequent Intake of Home Cooked Meals. A Cross-Sectional Survey Using the Validated Healthy Eating Index for Australian Adults (HEIFA-2013)

Abstract: Poor diet quality is commonly reported in young adults. This study aimed to measure the diet quality of students attending a large Australian university (including domestic and international students), and to examine the effect of food security status and other key factors likely to impact their diet quality. Using the Automated Self-Administered 24-h recall Australian version, a cross-sectional survey collected dietary recalls from domestic and international students in one university in Sydney. Diet quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(73 reference statements)
1
3
2
Order By: Relevance
“…Our study extends this research by demonstrating that food‐insecure students have significantly worse diet quality, in particular, fruit and vegetable quality scores, than that of their food‐secure peers. This is consistent with recent research conducted on another group of Australian university students that reported that food‐insecure, domestic‐enrolled students have significantly worse diet quality scores 10 . However, in that study, food‐insecure students reported consuming fewer wholegrains, and unlike our study, there were no differences in fruit and vegetable intake 10 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study extends this research by demonstrating that food‐insecure students have significantly worse diet quality, in particular, fruit and vegetable quality scores, than that of their food‐secure peers. This is consistent with recent research conducted on another group of Australian university students that reported that food‐insecure, domestic‐enrolled students have significantly worse diet quality scores 10 . However, in that study, food‐insecure students reported consuming fewer wholegrains, and unlike our study, there were no differences in fruit and vegetable intake 10 .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with recent research conducted on another group of Australian university students that reported that food-insecure, domestic-enrolled students have significantly worse diet quality scores. 10 However, in that study, food-insecure students reported consuming fewer wholegrains, and unlike our study, there were no differences in fruit and vegetable intake. 10 Discretionary food intake was not measured in our study, but it has been reported that food insecurity is also associated with higher intakes of sugar-sweetened beverages 35 and added sugars.…”
Section: Reference Rangecontrasting
confidence: 84%
See 3 more Smart Citations